UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN SAMBUNG NYAWA (Gynura procumbens) TERHADAP PERTUMBUHAN BAKTERI Pseudomonas aeruginosa DAN Staphylococcus epidermidis - Masyithah Thaib, Cut; Bemby Sinaga, Arman; Br Brahmana, Nettietalia; Sanjaya Sagala, Ranika (Universitas Sari Mutiara Indonesia, 2020)
Background : Antibacterial is a compound used to control the growth of harmful bacteria. Microorganism growth control aims to prevent the spread of disease and infection. The bacteria that cause infection are Pseudomonas aeruginosa and Staphylococcus epidermidis. The leaves are also believed to be efficacious as drugs in the treatment of kidney disease, dysentery, esophageal infection, stopping bleeding, launching menstruation, medicine for venomous animal bites, and swelling. The life-sustaining ethanol extract was positively correlated with its anti radical activity. The ethanol extract contains alkaloids, flavonoids, saponins, tannins, and steroids. Saponins, flavonoids, tannins and steroids are compounds that have antibacterial properties. Objective: This study was aimed to determine the antibacterial activity of the ethanolic extract of the grafted leaves (Gynura procumbens) against the growth of Pseudomonas aeruginosa AND Staphylococcus epidermidis bacteria. Methods: Extraction of the leaves of Connect Nyawa was carried out using the Masarasi method using 70% ethanol as a solvent. The ethanol extract obtained was phytochemical screening and antibacterial activity test against Staphylococcus epidermidis and Pseudomonas aeruginosa using agar diffusion method using disc paper with 3 repetitions and giving positive control of chloramphenicol and treatment with concentrations of 12.5%, 10%, 7.5 %, 2.5%, and 5%. The medium used as an antibacterial test was Mueller Hinton Agar (MHA). Results: The results of the simplicia characteristics of Connect Nyawa Leaves obtained water content of 0.886%, seawater content of 13.7%, ethanol soluble extract content of 16.06%, total ash content of 9.4%, acid insoluble ash content of 36.1%. Screening of extracts of life-long leaves and simplicia showed the presence of alkaloids, tannins, saponins, flavonoids, and steroids. The results of the bacterial activity test showed that the ethanol extract of life-sustaining leaves against Pseudomonas aeruginosa bacteria with concentrations of 12.5%, 10%, 7.5%, 2.5%, and 5%, each had an inhibitory zone with a diameter of 6.5 mm, 7 mm, 8.2 mm, 6 mm, 6 mm, while Staphylococcus Epidemidis. Conclusion: The result of this research is that the extract of the grafted life leaf (Gynura procumbens) has antibacterial activity against the growth of Staphylococcus epidermidis and Pseudomonas aeruginosa.